2008
DOI: 10.1021/jp710392k
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Phenylglycine- and Leucine-Derived Chiral Stationary Phases: Molecular Dynamics Simulation Study

Abstract: A theoretical study of the solvation of ( R)- N-(3,5-dinitrobenzoyl)phenylglycine- and ( R)- N-(3,5-dinitrobenzoyl)leucine-derived chiral stationary phases (CSPs) is presented. Semiflexible models of the chiral selectors are prepared from B3LYP/6-311G** calculations, and these are used in the molecular dynamics simulations of the corresponding interface. The chiral interface is examined for four solvents: 100% hexane, 90:10 hexane:2-propanol, 80:20 hexane:2-propanol, and 100% 2-propanol. Despite the similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…There are many options in carrying out MD simulations; for brevity we limit this discussion to atomistic simulations, which comprehensively explore the interactions between the chiral small molecules and the CSP. Factors to consider are: First, there is the option of including some representation of the solid support; (a) this could be treated as atomistically dynamic, an amorphous silica slab capped with silanols at the proper distribution of OH types in agreement with experiment for coated types of CSPs 32 or (b) a single layer of immoveable silicon atoms that represents silica, a rigid structure with surface atoms as tethering points for the selector molecule [32][33][34][35][36][37][38] ; the distribution of tethering points may be arbitrary, or regular, or else based on experimentally estimated grafting density in brush systems, for covalently bonded CSPs. For example, an interface could consist of trimethylsilyl end caps corresponding directly to a truncated selector tether, silanol groups, and selectors covalently attached to a single underlying layer of Si that is stationary throughout the simulation.…”
Section: Factors That Need To Be Considered In Designing the Simulamentioning
confidence: 99%
See 2 more Smart Citations
“…There are many options in carrying out MD simulations; for brevity we limit this discussion to atomistic simulations, which comprehensively explore the interactions between the chiral small molecules and the CSP. Factors to consider are: First, there is the option of including some representation of the solid support; (a) this could be treated as atomistically dynamic, an amorphous silica slab capped with silanols at the proper distribution of OH types in agreement with experiment for coated types of CSPs 32 or (b) a single layer of immoveable silicon atoms that represents silica, a rigid structure with surface atoms as tethering points for the selector molecule [32][33][34][35][36][37][38] ; the distribution of tethering points may be arbitrary, or regular, or else based on experimentally estimated grafting density in brush systems, for covalently bonded CSPs. For example, an interface could consist of trimethylsilyl end caps corresponding directly to a truncated selector tether, silanol groups, and selectors covalently attached to a single underlying layer of Si that is stationary throughout the simulation.…”
Section: Factors That Need To Be Considered In Designing the Simulamentioning
confidence: 99%
“…For example, an interface could consist of trimethylsilyl end caps corresponding directly to a truncated selector tether, silanol groups, and selectors covalently attached to a single underlying layer of Si that is stationary throughout the simulation. Alternately, the selector is grafted through an amide linkage to an aminopropyl siloxane-terminated Si(111) wafer, 39 or one could choose (c) not to include the solid support at all, instead compensate for the limited mobility of the polymer coated on solid support with restraining forces, 33,34 or (d) ignore the solid support and use a freely floating selector molecule or polymer fragment. 33,34 Second, there is the option of choosing the size of the selector fragment to use in the simulation; (a) for the polysaccharides some have used four 18-mer polymer strands, 32 (b) or a 12-mer single polymer strand, 33 (c) or even shorter strands, such as a 6-mer, 23 tetramer, dimer; use of a monomer (as in References 21,22) would not permit the analyte to feel the groove in the helical polymer structure.…”
Section: Factors That Need To Be Considered In Designing the Simulamentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the adsorption sojourn times and the number of adsorption-desorption or mass-transfer events can give a practical view of the molecular process of separation (2008) [163]. The studies of various kinds of molecular modeling for chiral separation by LC have been investigated extensively (2004)(2005)(2006)(2007)(2008)(2009) [164][165][166][167][168][169][170][171][172]. With researching the chiral recognition mechanisms at the molecular level, we can not only explain the experiment phenomena but also predict the results.…”
Section: Mechanism Of Chiral Recognitionmentioning
confidence: 99%
“…They found that the level of enantioselectivity was highly dependent on the molecular chain length and the position of the hydroxyl groups. Cann and coworkers simulated chiral separation on several stationary phases for liquid chromatography using molecular dynamics simulations and found that an increase of the alcohol concentration changed the preferred orientations of the selectors . In addition, Bao et al showed that different regions of an HMOF channel may present opposite enantioselectivities and that multiple chiral selectors packed in HMOF structures may work synergistically to improve the chiral separation effect .…”
Section: Introductionmentioning
confidence: 99%